2019
DOI: 10.1186/s12888-018-1959-5
|View full text |Cite
|
Sign up to set email alerts
|

Marte Meo as a port of entry to parental sensitivity - a three–case study

Abstract: BackgroundEarly parent- child relations play an important role in children’s development. Therapeutic intervention towards infants and toddlers at high-risk intends to prevent mental health problems. In this work, the parent-child-dyad is crucial. The video interaction guidance method, Marte Meo, is one among different methods used in attachment-based treatment in an outpatient infant mental health clinic. Parental sensitivity towards infants and toddlers needs is considered significant in developing secure at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…One study took a combined approach and used Marte Meo in interactions with both parents and teachers in preschools and primary schools (Balldin et al., 2018). Target groups were, with regard to the child in the interaction, children (3–12 years) with behavioural problems (Axberg et al., 2006; Balldin et al., 2018; Kristensen, 2005) and infants (Gill et al, 2019; Kristensen et al., 2017). Regarding the reference person, some studies targeted divorced fathers (DeGarmo et al., 2019) and burdened mothers of indigenous Australian origin (Lee et al., 2010) and mothers with postnatal depression (Vik & Braten, 2009; Vik & Hafting, 2009; Vik & Rohde, 2014).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One study took a combined approach and used Marte Meo in interactions with both parents and teachers in preschools and primary schools (Balldin et al., 2018). Target groups were, with regard to the child in the interaction, children (3–12 years) with behavioural problems (Axberg et al., 2006; Balldin et al., 2018; Kristensen, 2005) and infants (Gill et al, 2019; Kristensen et al., 2017). Regarding the reference person, some studies targeted divorced fathers (DeGarmo et al., 2019) and burdened mothers of indigenous Australian origin (Lee et al., 2010) and mothers with postnatal depression (Vik & Braten, 2009; Vik & Hafting, 2009; Vik & Rohde, 2014).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…However, many questions regarding the concrete application of the method remain open and unexplored (e.g. Gill et al, 2019). Therefore, the present article aimed to address this important and hitherto unexplored research topic of the Marte Meo method in counselling and describe the current state of use of Marte Meo.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Studies of mothers with postnatal depressive symptoms have shown how Marte Meo enhanced their vitality and invited them to self-reflection and other-centeredness in the presence of sensitive and attuned therapists. These studies have conceptually linked Marte Meo to Stern’s theories of early communication and mentalization, especially mentalized affectivity [ 9 , 10 ]. Quantitative studies have identified positive effects of Marte Meo on parental sensitivity, interaction, and infant development also within more vulnerable dyads [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several distinct methods have been developed, among them Marte Meo and its manualized variant called video feedback of parent–infant interaction (VIPI) (Onsoien, Drugli, & Hansen, 2015). Marte Meo is used in four continents, and more widely implemented in several European countries as well as Australia, and improves parent–infant interaction, parental sensitivity, and infant development also in more vulnerable dyads (Gill, Thorød, & Vik, 2019; Høivik et al., 2015; Kristensen, Simonsen, Trillingsgaard, & Kronborg, 2017). It originated out of an intersubjective perspective and, like video‐interaction guidance (VIG) (Kennedy, Landor, & Todd, 2011), has a decidedly solution‐focused stance, omitting material that shows negative or ineffectual interaction.…”
Section: Introductionmentioning
confidence: 99%